Management and Financial Governance Training For Becak Kopi Operations as Mobile Coffee Stalls Marketing Solution: Pelatihan Tata Kelola Manajemen Dan Keuangan Operasional Becak Kopi Sebagai Solusi Pemasaran Angkringan Kopi Kelana - Dharmayanti Pri Handini; Gatot Soebiyakto; Nurida Finahari (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Training programs are still seen as a common community service activity to be carried out. The measures of its effectiveness are not widely studied before the activity is carried out, as are the chances of success and sustainability. The training on operational management and financial governance conducted by the TTG Mechanical Engineering Team of Widya Gama University of Malang, was designed by studying the success factors of a training. This training is specifically aimed at supporting the process of developing partner businesses to open a coffee stall that moves following market movements. The understanding of the training participants has been measured well before the presentation of the material, especially regarding the theories and practical applications of the material presented. However, several aspects of the material related to the concept of a coffee stall that is not yet understood at all. The participants' understanding is still focused on the fixed stall model. The results of the training show that in order to be applied to support the process of operating a coffee stall that is Kelana, partners need to apply the theories taught in the training into a standardized operational system. This will be followed up in the next activity.